Shisha smokers’ determinants of use, knowledge and perception towards shisha (waterpipe) smoking in Penang, Malaysia - Elkalmi, Ramadan Mohamed Mahmod; Elsayed, Tarek M.; Alkoudmani, Ramez M.; Al-lela, Omer Qutaiba B.; Jamished, Shazia Q.; Awad, Ammar I.; Mohamad Haniki , Nik Mohamed; Alshami , Abdul Karim (2015)
Background: Tobacco smoking is a serious health problem worldwide. Malaysia as many of south Asian countries faces the challenge of rising tobacco consumption. Despite the apparent spread of Shisha smoking phenomenon among Malaysian population, little is known about the safety concerns and determinants of Shisha smokers in this community. Objectives: This study aimed to determine the social determinants of Shisha smoking among Malaysian population in Penang Island, Malaysia and to explore their health related knowledge and perception toward Shisha smoking. Methods: The survey was conducted using simple random sampling by randomly distributing self-administered questionnaires to consumers in Shisha lounges located in Penang Island. Statistical analyses were performed using the Statistical Package for Social Science (SPSS) version 20. Results: A total number of 171 (42.75%) of respondents participated in this study. Mean age was 21.5±4.4 years. The majority were male, Malay (79.6%, 63.1% respectively). About 97.1% of respondents smoke Shisha either alone or with tobacco cigarettes. The majority (63.1%) started Shisha smoking at an age ≤ 20 years old, always in a café' (72.2%), share Shisha smoking with others (81.6%). Only 35.9% of respondents reported smoking Shisha daily. 71% reported smoking ≤ 7 bowls per week. 50.5% claimed smoking Shisha for more than 60 minutes per session. Boredom, outing and meeting with friends and family ranked first among the motives for smoking Shisha. Regarding knowledge about Shisha smoking, the majority believes that cigarettes are more harmful, more addictive and has more nicotine than waterpipe (60.2%, 71.8% and 67%; respectively). A large proportion (66%) of respondents believes that Shisha smoking doesn't transmit hepatitis infection. The majority of respondents perceived Shisha smoking acceptable by society and parents, compared to cigarettes (67% and 60.2%; respectively). The vast majority of respondents believe that Shisha smoking relieves stress and tension (77.7%), while the minority believes that Shisha smokers have more friends than non-smokers. Regarding access to Shisha, half of respondents agreed that Shisha is easily accessible than cigarettes. The majority of respondent foresees increasing popularity of Shisha smoking in the next 5 years (83.5%). Conclusion: This study showed that there is a high prevalence of Shisha smoking among the Malaysian youth associated with false believes about its health effects. Further studies involving larger population are encouraged.